Stability of murine bradykinin type 2 receptor despite treatment with NO, bradykinin, icatibant, or C1‐INH. Issue 3 (24th December 2014) - Khosravani, F.; Suvorava, T.; Dao, V. T.‐V.; Brockmann, N.; Kocgirli, O.; Herbst, F. F.; Valcaccia, S.; Kassack, M. U.; Bas, M.; Kojda, G.
Abstract Background Little is known about factors which trigger and/or contribute to hereditary angioedema or ACE‐inhibitor‐mediated angioedema including variations in bradykinin type 2 receptor (B2R) expression and activity. Methods Protein and mRNA expression of B2R and the increase of intracellular calcium (iCa) in response to bradykinin were monitored in porcine and murine endothelial cells in response to NO donors or bradykinin. B2R protein expression was evaluated in skin, heart, and lung of (i) mice with endothelial‐specific overexpression of eNOS (eNOStg), (ii) in eNOS−/− mice and (iii) in C57BL/6 mice treated with the NO donor pentaerythritol tetranitrate (PETN), the NOS inhibitor l‐nitroarginine (L‐NA), plasma pool C1‐INH, and the B2R antagonist icatibant. Aortic reactivity to bradykinin was investigated including eNOS−/− mice. Results B2R protein and mRNA expression remained unchanged in cells subjected to L‐NA, NO donors, and bradykinin in a time‐ and concentration‐dependent manner. Likewise, increases of iCa in murine brain endothelial cells remained unchanged. B2R protein levels were similar in eNOStg and eNOS−/− as compared to transgene‐negative littermates. Likewise, treatment of C57BL/6 mice with PETN, L‐NA, C1‐INH or icatibant did not change B2R protein expression. In aortic rings of C57BL/6 mice, bradykinin induced B2R‐dependent constrictions which were attenuated by endothelial NO and abolished by diclofenac indicating the functional importance of B2R‐induced activation of endothelial NO synthase and cyclooxygenase. Conclusion These data suggest that alterations of B2R protein expression induced by NO, bradykinin, C1‐INH, or icatibant unlikely contribute to bradykinin‐induced angioedema. This finding does not rule out a role for NO in bradykinin‐induced extravasation and/or angioedema.